Foliar Fertilization of Different Species of Mulberry Trees and Its Impact on Silkworm Bombyx mori Productivity from Cocoons and Eggs - sawsan abdelmegeed (Arab Universities Journal of Agricultural Sciences, 2021)
Rearing mulberry silkworm was found to be dependent on leaves quality of mulberry trees, larvae of mulberry silkworm fed on two species of mulberry trees Morus alba and Mo-rus nigra were treated with foliar fertilizer (Basfoliar 20-19-19 SP contains 20% N, 19% P2O5, 19% K2O, 5% NO3, 3.6% NH4 and 11.4% NH2) with three different concentra-tions,1%, 3% and 6% in addition to control treatment for comparison. When larvae were fed on leaves of mulberry trees one day after Treatment, high mortality (up to 100%) was observed specially with 6% concentration. Mean weights of larvae, cocoons and cocoon shell and fecundity were negatively affected when compared to control. On the other hand, when larvae were fed on leaves of mulberry trees, no mortality occurred after two weeks of treatment in all concentrations, in addition, the mean weights of larvae at the end of 4th and 5th instar larvae, cocoons and cocoon shell s in-creased at 3% concentration compared with other concentrations and control. The highest fecundity occurred in female moths when lar-vae were fed on leaves of M .nigra compared with M. alba as well as 3% concentration com-pared with other concentrations and control.